Analisis Peran E-Commerce dalam Meningkatkan Perkembangan Bisnis pada Wirausaha Berskala Mikro di Kabupaten Sidoarjo - Arif Azmi; Wulandari Harjanti; Sri Wahyuni (PUTRA JAWA PUBLISHER, 2024)
This study aims to analyse the role of e-commerce in improving business development in micro-scale entrepreneurs in Sidoarjo Regency. E-commerce has become one of the solutions for entrepreneurs to expand markets and increase sales without being limited by geographical location. The research method used is descriptive quantitative, with data collection through questionnaires distributed to 100 micro-entrepreneurs in Sidoarjo Regency. The results show that the use of e-commerce significantly has a positive impact on increasing sales, operational efficiency, and market access. In addition, e-commerce also helps micro-entrepreneurs in facing the challenges of competition with larger businesses. Thus, e-commerce implementation is an important strategy for micro-entrepreneurs in Sidoarjo Regency to consider in order to improve their competitiveness and business growth.